Coherent vibrational dynamics in ethylene carbonate: insights from 2D infrared spectroscopy - Guerrieri, Luke Robert, author; Krummel, Amber T., advisor; Levinger, Nancy, committee member; Wilson, Jesse, committee member; Henry, Chuck, committee member (Colorado State University. Libraries, 2025)
The research presented in this dissertation explores the mechanisms of coherent vibrational relaxation in the cyclic carbonate ester, ethylene carbonate (EC). Coherent relaxation processes describe the redistribution of quantum superposition states, but relatively little is known about the molecular properties governing these processes for vibrational superpositions in chemical systems. EC, a highly coupled vibrational system with applications in organic battery electrolyte mixtures, serves as a model compound for studying coherent vibrational dynamics. The fundamental carbonyl stretch of EC couples to doubly excited states via Fermi resonance. An investigation of the carbonyl fundamental stretch using linear Fourier transform infrared spectroscopy (FTIR) and two-dimensional infrared spectroscopy (2DIR) reveals coherent relaxation mechanisms involving multiple vibrational degrees of freedom. Pump selective 2DIR experiments compare the relative intensities of coherent relaxation processes to different features in the 2DIR spectrum, finding a correlation between the spectral amplitude of coherent relaxation processes and Fermi resonance coupling strength. A follow up investigation uses 13C isotopic substitution to modify the Fermi resonance coupling strength in EC isotopologues. It is found that 13C substitution strengthens the Fermi resonance coupling in EC isotopologues; however, isotopic substitution is found to suppress the redistribution of quantum superpositions involving Fermi coupled vibrations. Analysis of vibrational lifetimes for the Fermi coupled states indicates that the relative strengths of coherent relaxation processes correlate with the strength of vibrational coupling to a manifold of experimental dark states. Those results suggest that coherent relaxation in EC is primarily driven by the delocalization of vibrational relaxation pathways, rather than the strength of direct coupling between Fermi coupled modes.
Keywords: nonlinear spectroscopy; 2DIR